'C'est à ce prix que vous mangez du sucre en Europe': Decolonizing plantationocene visualities in Amalia Ramanankirahina's Le grand couvert. (1st September 2022) - Matheron, Aurélie
This article explores how the installation Le grand couvert by Malagasy artist Amalia Ramanankirahina intersects colonial plantations and a French Parisian orchard to decolonize contemporary French ecological thinking. As this article explores how French rural ecologies are embedded within a wider variety of environments and their violent plantationocenic histories, it argues that Le grand couvert performs 'aesthetic marronage', a form of fugitivity that breaks through 'traditional' plantation visual cultures ‐ ones that freeze plantations into a space of leisure and exoticism, albeit a violent one. Tracing the contours of the material, economic and ecological, 'legacies' of the plantationocene in and across contemporary France and its overseas territories, this article ultimately demonstrates how Le grand couvert helps interrogate what Stephanie Posthumus has called 'ecological dwelling', the evolving processes of bodies in and with space. While Posthumus understands ecological dwelling primarily along urban/rural paradigms, Ramanankirahina's decolonial work injects new perspectives on this concept. In Le grand couvert, the plantation bleeds into the colonial space of a former rural space now known as a banlieue. At the intersection of the plantation and the banlieue, aesthetic marronage reveals the tensions of dwelling ecologically in sites that racially and economically restrict one's subjective formation.